Pengembangan Media Pembelajaran Ular Tangga Pada Mata Pelajaran Matematika Materi Pecahan Campuran Di Kelas VB SDN PANCORAN 07 PAGI JAKARTA - Fitri Noviana; Satriyani, Febrianti Yuli (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2025)
The research method used is the research and development method (Research and Development) which refers to the formulation of Dick and Carey with stages: 1) Identifying instructional needs and writing general instructional objectives 2) Instructional analysis 3) Identifying behavior and initial learner characteristics 4) Writing specific instructional objectives5) Developing learning outcomes assessment tools 6) Developing instructional strategies 7) Develop instructional materials 8) Design and carry out formative evaluation 9) Instructional System 10) Implementation of Summative Evaluation and Diffusion of Innovation. character is carried out by distributing questionnaires to expert validators and respondents. The results obtained from the design expert get a percentage of 82%